2012
DOI: 10.1590/s2237-93632012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of Epstein-Barr virus, cytomegalovirus, herpes simplex virus, human papillomavirus and anal intraepithelial neoplasia in HIV patients in Amazon, Brazil

Abstract: OBJECTIVE: The prevention of anal cancer is a goal of worldwide Aids support centers. Despite the efforts that have been made and progress in the antiretroviral therapy, effective disease control remains elusive. Difficulty in preventing anal cancer may result from the ineffectiveness of highly active antiretroviral therapy on the human papillomavirus (HPV) since the coinfection with HIV and HPV appears to increase the risk of HPV-infected cells, becoming cancerous. METHODS: We evaluated 69 HIV-positive and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(28 reference statements)
0
8
0
1
Order By: Relevance
“…For example, high-risk HPV/HSV-2 co-infections were present in the anorectum of 55% of Brazilian MSM. Corresponding values for other combinations in that study were 27% (high-risk HPV/low-risk HPV/EBV), 9% (high-risk HPV/low-risk HPV/HSV2/EBV) and 9% (high-risk HPV/low-risk HPV/HSV-1/HSV-2/EBV) [ 11 ]. HPV and HSV co-infections were found in 4.3% of oral samples from Finnish males [ 50 ].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…For example, high-risk HPV/HSV-2 co-infections were present in the anorectum of 55% of Brazilian MSM. Corresponding values for other combinations in that study were 27% (high-risk HPV/low-risk HPV/EBV), 9% (high-risk HPV/low-risk HPV/HSV2/EBV) and 9% (high-risk HPV/low-risk HPV/HSV-1/HSV-2/EBV) [ 11 ]. HPV and HSV co-infections were found in 4.3% of oral samples from Finnish males [ 50 ].…”
Section: Discussionmentioning
confidence: 92%
“…Most studies of HSV infection in MSM have reported only seroprevalence (82.5–90%) [ 47 , 48 ]. However, a few studies have reported prevalence of HSV DNA in the anorectum (ranging from 7.0 to 16.9%), oropharynx (0–7.2%) and urethra (2.3–49.5%) among MSM [ 11 , 34 , 49 51 ]. Consistent with previous studies, we found very low prevalence of HSV in all three sites (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As DST podem causar infertilidade 5 , câncer cervical 6 , anal 7 e de pênis 8 . Ademais, podem aumentar o risco de infecção pelo HIV 9 .…”
unclassified